A review of oscillating screen-blower cleaners for grains. - Pasikatan, Melchor C. (Philippine Engineering Journal)
The literature concerned with grain or seed cleaners using blower and linearly oscillating screens, and related machines and mechanisms was reviewed. Attempts in developing the theory and mechanics of cleaners was discussed. Grain, straw and chaff aerodynamic and mechanical properties which affect separation were assessed. The potentials and limits of pure aerodynamic separation, effects of design, operating and material parameters on cleaning performance were critically examined. The available information may be limited, but sufficient to provide rough parameters for design under different operating conditions. Researches show that to achieve good cleaning performance at high material capacity in wheat and paddy, air velocity of 7.2-9.2 m/s, air direction of 40-45 degrees, height of drop of 70-102 mm, and hanger angles of 15-25 degrees should be used. Attempts to relate cleaning performance with two or more influencing factors are rare in the literature. Results derived with wheat and based on straw walker and shoe assembly of combines need to be validated for rice, rice threshers and cleaners. Further studies that will lead to a universal cleaning equation and a good understanding of particle motion as influenced by several variables are needed.